2020
DOI: 10.1101/2020.01.07.897876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The copy-number and varied strengths of MELT motifs in Spc105 balance the strength and responsiveness the Spindle Assembly Checkpoint

Abstract: The Spindle Assembly Checkpoint (SAC) maintains genome stability while enabling timely anaphase onset. To maintain genome stability, the SAC must be strong so that it delays cell division even if one chromosome is unattached, but for timely anaphase onset, it must be responsive to silencing mechanisms. How it meets these potentially antagonistic requirements is unclear. Here we show that the balance between SAC strength and responsiveness is determined by the number of 'MELT' motifs in the kinetochore protein … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…Negative PRD scores can be interpreted as "more conserved than average", such as the cell cycle protein CDC20 (-0.15) that has a constrained beta propellor fold (Yu 2007;Xu and Min 2011) . As expected, KNL1 (#20, Figure 4a) and PRDM9 (#14) have especially fast evolving repeats (Schwartz et al 2014;Tromer et al 2015;Roy et al 2020) .…”
Section: Distribution Of Ogs With Prd Scores (X-axis Symlog) Shows Thsupporting
confidence: 69%
See 2 more Smart Citations
“…Negative PRD scores can be interpreted as "more conserved than average", such as the cell cycle protein CDC20 (-0.15) that has a constrained beta propellor fold (Yu 2007;Xu and Min 2011) . As expected, KNL1 (#20, Figure 4a) and PRDM9 (#14) have especially fast evolving repeats (Schwartz et al 2014;Tromer et al 2015;Roy et al 2020) .…”
Section: Distribution Of Ogs With Prd Scores (X-axis Symlog) Shows Thsupporting
confidence: 69%
“…For example, in KNL1 the rapid evolution of the motif repeat region seems to be adaptive and result from balancing the strength of motif binding and responsiveness leading to a varying selection pressure (Roy et al 2020) . In addition, because (i) there is also no clear mutational bias, (ii) most repeats are stably conserved, and (iii) purifying selection seems to be active on proteins with dynamic repeats (as inferred from ExAC and Selectome), it is possible that those repeats that are rapidly evolving, do so for adaptive reasons which still would need to be elucidated.…”
Section: Comparison Of Rapid Repeat Evolution To Other Rapid Evolutiomentioning
confidence: 99%
See 1 more Smart Citation
“…In human cells, Mad1 recruitment is possible when two conserved sites, S459 and T461 of Bub1 (T453 and T455 in budding yeast Bub1), are phosphorylated by Cdk1 and Mps1 respectively [5, 6]. Previous results showed that mutation of these two residues in yeast (bub1 T453A, T455A ) decreased Mad1 recruitment to unattached kinetochores only modestly, and did not affect the strength of SAC signaling in nocodazole-treated cells [27]. Consistently, the same mutations had no effect on the ability of Mps1 to ectopically activate the SAC in budding yeast (Fig S1E left).…”
Section: Resultsmentioning
confidence: 99%
“…As the appropriate model for this condition, we used cells expressing spc105 RASA , a well-characterized mutant of Spc105/KNL1 that cannot recruit Protein Phosphatase 1 via the ‘RVSF’ motif proximal to its N-terminus. In cells expressing spc105 RASA , the SAC remains active in metaphase even after kinetochore biorientation because of a greatly diminished PP1 activity [27, 32, 36]. As a result, Bub3-Bub1 is not removed from metaphase kinetochore even though the ability of Mps1 to phosphorylate Spc105 is also diminished due to the formation of stable kinetochore-microtubule attachments [14].…”
Section: Resultsmentioning
confidence: 99%